Nationalism in Danger: A Risk of Implementing Governance in Unequal Power Relation - Purnomo, Joko (Jurnal Interaktif, 2010)
The idea of governance has successfully gained its popularity in Indonesia. The government, private enterprises and society welcome and embrace the idea of governance as a final solution to maintain development. In this paper, it is argued that the implementation of governance can not guarantee the fulfillment of societyâs interest due to the existence of unequal power relation embedded in countryâs political environment. The concept of Governance, moreover, can be claimed as an imperialist instrument since this concept has strong interconnection with neo liberal agenda. Indeed, Governance as new imperialism will reduce nationalism. Key words: Governance, Hegemony, Nationalism, Imperialism.